Cellulose triacetate films obtained from sugarcane bagasse: Evaluation as coating and mucoadhesive material for drug delivery systems. (5th November 2016) - Ribeiro, Sabrina Dias; -->Rodrigues Filho, Guimes; Meneguin, Andréia Bagliotti; Prezotti, Fabíola Garavello; Boni, Fernanda Isadora; Cury, Beatriz Stringhetti Ferreira; Gremião, Maria Palmira Daflon
Highlights: Cellulose triacetate (CTA) films were produced from cellulose extracted sugarcane bagasse. Films showed potential for using as coating and mucoadhesive. Coated particles released 100% of the ketoprofen in 24 h, uncoated particles released 100% in 4 h. The results highlight the potential of CTA in the development controlled oral delivery systems. Abstract: Cellulose triacetate (CTA) films were produced from cellulose extracted from sugarcane bagasse. The films were characterized using scanning electron microscopy (SEM), water vapor permeability (WVP), mechanical properties (MP), enzymatic digestion (ED), and mucoadhesive properties evaluation (MPE). WVP showed that more concentrated films have higher values; asymmetric films had higher values than symmetric films. MP showed that symmetric membranes are more resistant than asymmetric ones. All films presented high mucoadhesiveness. From the WVP and MP results, a symmetric membrane with 6.5% CTA was selected for the coating of gellan gum (GG) particles incorporating ketoprofen (KET). Thermogravimetric analysis (TGA) showed that the CTA coating does not influence the thermal stability of the particles. Coated particles released 100% of the KET in 24 h, while uncoated particles released the same amount in 4 h. The results highlight the CTA potential in the development of new controlled oral delivery systems.